2015
DOI: 10.1136/bjophthalmol-2015-306672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and survival of retinoblastoma in Indian children

Abstract: Delayed presentation is a matter of concern. Improving awareness about the early signs and creating facilities for diagnosing and treating RB at the primary and secondary levels of healthcare are required to reduce mortality and morbidity, and lead to improved outcomes that are comparable with the developed nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
120
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 24 publications
24
120
4
Order By: Relevance
“…The average age at presentation of our patients (∼35 months) is comparable to the range of 29-33 months in previous reports from India [3,12,14]. It is also similar to studies from other medium Human Development Index (HDI) countries like Egypt [15] (36 months) and Mali [16] (50 months).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The average age at presentation of our patients (∼35 months) is comparable to the range of 29-33 months in previous reports from India [3,12,14]. It is also similar to studies from other medium Human Development Index (HDI) countries like Egypt [15] (36 months) and Mali [16] (50 months).…”
Section: Discussionsupporting
confidence: 74%
“…There is a definite regional bias in studies from our country as males were generally preferred for treatment in earlier studies as well [3]. Being a tertiary care center, we largely get referrals of children from local hospitals, and it is alarming to note that health problems in female children are often ignored and undetected [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, median age of presentation was 24 months which is comparable with previous other studies from North India (29 months), Iran (28.5 months), Taiwan (26.3 months) and Malaysia (24.2 months). 15,20,21 A relatively higher median age at diagnosis has been reported from African countries like Ghana (36 months) and Kenya (37.5 months). 14,22 Tumours were relatively diagnosed at an earlier age in Australia and USA.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In North India, Bhavna et al, reported a survival probability of 83%, 73% and 65% at 1 year, 2 years and 5 years, respeactively. 15 A comprehensive multimodality treatment is pertinent in RB to improve outcomes. The term chemoreduction is used to describe the technique of using chemotherapy to reduce the retinal tumor size for better control.…”
mentioning
confidence: 99%